1989
DOI: 10.2307/145820
|View full text |Cite
|
Sign up to set email alerts
|

Why So Many Children of Doctors Become Doctors: Nepotism vs. Human Capital Transfers

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. University of Wisconsin Press and The Board of Regents of the University of WisconsinSystem are collaborating with JSTOR to digitize, preserve and extend access to The Journal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
66
0
4

Year Published

1991
1991
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(80 citation statements)
references
References 14 publications
5
66
0
4
Order By: Relevance
“…There were however few studies that assess the generic factors which make Medicine itself of interest to medical students and to potential Medicine students specified by Livingstone MM et al 15 In the present study there were more male students in comparison to females as shown in Table 1, but in the study done by Ferimann there was the increasing proportions of female students and about the problems in medical school of male and ethnic minority students quoted by Wars V, Robert et al 17,18 There had also been a growing awareness that medical students typically come from relatively high social classes as quoted by Grenhalgh, Seyan and Boynton and Mc Manus, many from Medical families Horton, Lents and Laband, Mc Manus, Billings and concern that such individual have different motivations and interests in medicine as a career stated by Gough, Mc Manus, Lurngston and Kotana. 15,[19][20][21][22][23][24][25] In the present study also there was higher high socio economic status group. In the present study father's education was graduation and post-graduation 43 (41.35%) and 29 (27.89%) which was similar to the study done by Hunkar Korkaz in which most fathers were educated with a university degree and the fathers worked in professional occupations.…”
Section: Resultsmentioning
confidence: 66%
“…There were however few studies that assess the generic factors which make Medicine itself of interest to medical students and to potential Medicine students specified by Livingstone MM et al 15 In the present study there were more male students in comparison to females as shown in Table 1, but in the study done by Ferimann there was the increasing proportions of female students and about the problems in medical school of male and ethnic minority students quoted by Wars V, Robert et al 17,18 There had also been a growing awareness that medical students typically come from relatively high social classes as quoted by Grenhalgh, Seyan and Boynton and Mc Manus, many from Medical families Horton, Lents and Laband, Mc Manus, Billings and concern that such individual have different motivations and interests in medicine as a career stated by Gough, Mc Manus, Lurngston and Kotana. 15,[19][20][21][22][23][24][25] In the present study also there was higher high socio economic status group. In the present study father's education was graduation and post-graduation 43 (41.35%) and 29 (27.89%) which was similar to the study done by Hunkar Korkaz in which most fathers were educated with a university degree and the fathers worked in professional occupations.…”
Section: Resultsmentioning
confidence: 66%
“…Thus it has been di¢ cult to identify whether a group's higher earnings are due to higher productivity or due to discrimination by employers. 18 For instance, Lentz and Laband (1989) …nd that college graduates who are the children of medical doctors tend to enjoy a 10% greater probability of admission to medical school, conditional on a number of controls. However, Chevalier (2001) attributes the relatively higher earnings of British graduates with the same career choice as their parents to the intergenerational transmission of human capital.…”
Section: Related Literaturementioning
confidence: 99%
“…Given that our candidates took the exam within the last ten years, and that candidates could be as young as 23 years of age but are usually not much older than 30 (Bagues 2005, Bagues and Esteve-Volart 2007b), 32 we can restrict Corps members in our analysis to those born before 1960. 33 In Table 3 we show the number of Corps members (…rst row), the number of Corps members who were born before 1960 (and thus are relevant to our analysis) (second row), and the number of male Corps members born before 1960 (third row).…”
Section: Degree Of Kinshipmentioning
confidence: 99%
“…Lentz and Laband (1989) document a 14% increase in the likelihood of being accepted to medical school among the children of doctors that cannot be explained. Scoppa (2009) finds evidence that in Italy the children of public sector employees have a substantial advantage in gaining employment in public sector jobs themselves.…”
Section: Introductionmentioning
confidence: 99%